The Effectiveness of the Simpati Program in Preventing Stunting: A Digital Solution for a Healthy Generation in Sumedang Regency - Lalas Sulastri; Irma Hermayanty (Department of Public Administration, 2025)
This study aims to analyze the effectiveness of the SIMPATI application as a digital innovation for stunting prevention in Sumedang Regency using a qualitative case study approach. The evaluation adopts Wirawan’s policy evaluation framework, covering three key dimensions: process, benefit, and impact. Data were collected through in-depth interviews, participatory field observations, and documentation involving health workers, posyandu cadres, mothers of toddlers, and local government officials. The findings show that SIMPATI contributes positively to real-time child nutrition monitoring, increases mothers’ participation in posyandu, and improves the accuracy and speed of data recording and service delivery. From a process perspective, SIMPATI supports better coordination among stakeholders despite infrastructure and digital literacy challenges. From a benefit perspective, it facilitates health awareness, improves user experience, and enhances data access. From an impact perspective, the program has led to increased maternal engagement and a decline in the number of children at risk of stunting over six months. However, issues such as limited infrastructure and human resource readiness remain obstacles to long-term sustainability. The study recommends enhancing digital infrastructure, conducting regular training, and strengthening multi-sectoral collaboration to ensure the successful scaling of SIMPATI as a national stunting prevention model.